WHO'S GLOBAL NUTRITION CAMPAIGN ON INSTAGRAM: VISUAL COMMUNICATION STRATEGY AND STRENGTHENING DIGITAL NUTRITION LITERACY - Yeyep Natrio; Wilda Laila; Yensasnidar Yensasnidar (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2026)
This study investigates how the World Health Organization (WHO) uses visual communication strategies on Instagram to promote global dietary risk reduction and enhance digital nutritional literacy within the community. Using a descriptive qualitative method, the study analyzes 13 infographics posted by @who from August 2025 to May 2026, selected through purposive sampling. The data analysis combines the qualitative framework of Miles, Huberman, and Saldaña with multimodal discourse analysis based on Kress and van Leeuwen's Visual Grammar. Results indicate that WHO effectively employs flexible and causal visual grammar to clarify complex macronutrient issues, such as using engaging imperative sentences to promote reduced sugar and salt intake. Additionally, the study reveals a transition in WHO's Instagram role from serving as a digital info board to functioning as a policy advocacy platform, encouraging health taxes at the national level. This research highlights that successful health promotion depends on visual adaptations that reduce psychological resistance from digital audiences while fostering their ability to critically evaluate nutritional information online.